Variation Feature, Pollution Risk Assessment, and Source Analysis of Heavy Metals in Lanzhou City, Northwestern China. (18th July 2022) - Zeng, Yongyao; Zhou, Bo
Abstract : Lanzhou is located in the northwest of China and is famous for its petrochemical and heavy industries of China. The city has suffered long-term pollution of heavy metals in recent years. Significant efforts, such as tax subsidies for new energy vehicles and treating solid waste, have been launched by the Lanzhou municipal government to address the pollution of heavy metals since 2010. What is the current status of heavy metal pollution in Lanzhou? In this study, the concentrations of 12 heavy metals (V, Cr, Mn, Co, Ni, Cu, Zn, As, Mo, Cd, Sb, and Pb) were tested from 20 sediment samples. Mn, Zn, V, and Cr are the predominant heavy metals, with mean concentrations of 534.65, 65.85, 56.29, and 36.05 mg/kg; Ni, Cu, Pb, Co, and As are in moderate amounts, with mean concentrations of 25.2, 21.5, 16.7, 9.87, and 4.86 mg/kg; Mo and Cd have the lowest mean concentrations of 0.54 and 0.15 mg/kg. A low ecological risk is confirmed by two indices, the Hakanson potential ecological risk index (R I ) and the geoaccumulation index (I geo ). The R I index has lower E i r values (<40) and R I values (<150), which range from 18.11 to 37.95, with an average value of 25.61. Co, V, Cd, Cu, Zn, As, Cr, Ni, Pb, and Mn metals are classified as an uncontaminated environment (level 0) and a moderately to heavily contaminated environment (level 2-level 3) by I geo values. Seven heavy metals (Pb, Cd, Cr, As, Cu, Zn, and Ni) in Lanzhou are the relatively lowest amount in the 5 cities in China. The changing trends of heavy metal concentrations firstly increase and then decrease gradually from 2005 to 2022. The time turning point of concentration shrinking occurred in approximately 2014, which is in response to the increased efforts of addressing the pollution launched by the Lanzhou municipal government since 2010. Source analysis by Pearson's correlation and principal component analysis revealed that the accumulation of Mo metal was caused by the enrichment of MnO2 in the oxidic condition; the accumulations of Cu, Co, Ni, Mn, Cr, Zn, Cd, and Pb metals are influenced by natural sources and human activities (vehicle exhaust and industrial pollution), respectively.